Words Will Never Hurt Me?: Preferred Terms for Describing Obesity and Binge Eating - Lydecker, Janet A. (Int J Clin Pract, 2016)
OBJECTIVE: This study evaluated individuals’ language preferences for discussing obesity and binge eating. METHOD: Participants (N=817; 68.3% female) were an online community sample. They rated the desirability of terms related to obesity and binge eating, and also completed psychometrically-established eating-disorder measures. In addition to examining participants’ preferences, analyses explored whether preferences differed by socio-demographic variables, weight status, and binge-eating status. RESULTS: Preferred obesity-related terms were weight and BMI, although women rated undesirable obesity-related terms even lower than did men. Participants with obesity and binge eating rated weight, BMI, unhealthy BMI, and large size as less desirable than participants with obesity but not binge eating. Binge-related terms were generally ranked positively; preferred descriptions were kept eating even though not physically hungry and loss of control. CONCLUSIONS: Preferred terms were generally consistent across sex, weight status, and binge-eating status. Using terms ranked more preferably and avoiding terms ranked more undesirably may enhance clinical interactions, particularly when discussing obesity with women and individuals reporting binge eating, as these groups had stronger aversion to some non-preferred terms. Findings that the selected binge-related descriptions were rated neutrally on average provide support for their use by clinicians.